2018
DOI: 10.1093/ajh/hpy074
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of TLR4 Within the Paraventricular Nucleus Attenuates Blood Pressure by Regulating ROS and Inflammatory Cytokines in Prehypertensive Rats

Abstract: Salt-induced prehypertension is partly due to the upregulation of TLR4 in PVN. Blockade of TLR4 in the brain reduced salt-induced prehypertension response, possibly through downregulation of ROS and PICs expression, and the restorage of neurotransmitter balance in the PVN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…Increased ROS production can be found in the PVN of hypertensive animals (Wang et al, 2018(Wang et al, , 2021Yang et al, 2020). The oxidative stress caused by the imbalance of ROS production and removal contributes to the advancement of inflammatory responses and hyperactivity of sympathetic nerves, and promotes the progression of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Increased ROS production can be found in the PVN of hypertensive animals (Wang et al, 2018(Wang et al, , 2021Yang et al, 2020). The oxidative stress caused by the imbalance of ROS production and removal contributes to the advancement of inflammatory responses and hyperactivity of sympathetic nerves, and promotes the progression of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…TLR4 has been recognized as an important regulator for NF-κB (Li et al, 2016). Growing pieces of evidence have shown that activated TLR4 within the PVN contributes to RSNA in salt-sensitive hypertension, by which the MyD88 is activated and subsequentially lead to the activation of NF-κB (Li et al, 2016; Wang M.L. et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…ROS can act as key modulators of increased neuronal activity in the PVN of rats with hypertension, heart failure or metabolic syndrome [2932]. More importantly, ROS in the PVN can modulate AAR [25].…”
Section: Discussionmentioning
confidence: 99%